Curcumin contributes to in vitro removal of non-transferrin bound iron by deferiprone and desferrioxamine in thalassemic plasma - Srichairatanakool S. (2014)
Non-transferrin-bound iron (NTBI) is detectable in plasma of β-thalassemia patients with transfusional iron overload. This form of iron may cause oxidative tissue damage and increased iron uptake, into several vital organs. Removal of NTBI species is incomplete and transient using standard intermittent desferrioxamine (DFO) or deferiprone (DFP) monotherapy. Combinations of these or other chelators may improve the protection time from NTBI and increase removal of harmful NTBI species. Curcuminoids from Curcuma Ionga L. is a naturally occurring phytochemical which shows a wide range of pharmacological properties including anti-oxidative, anti-inflammatory, anti-cancer and iron-chelating activities. In this study, the curcuminoids was investigated for NTBI chelation in thalassemic plasma in vitro and for the potential to improve NTBI removal when used with other chelators. Curcumin bound Fe3+ to form a Fe3+-curcumin complex with a predominant absorption at 500 nm. The chemical binding of curcumin was dose- and time-dependent and more specific for Fe3+ than Fe2+. Using a HPLC-based NTBI assay without an aluminium blocking step, curcumin shuttled the iron from Fe3+-NTA complex, giving underestimated NTBI values. At equivalent concentrations DFO, DFP and curcumin decreased plasma NTBI with the order of DFP>DFO>curcumin. None of these chelators removed NTBI completely, but curcumin appeared to increase the rate of NTBI removal when added to DFP. It is proposed that the β-diketo moiety of curcumin participates in the NTBI chelation. © 2007 Bentham Science Publishers Ltd.